Methodological and Theoretical Foundations of Family Values - Mamadiyarova Malika (Indonesian Journal of Social Development, 2025)
In the current rapidly changing world, especially in rapidly developing social systems, man is constantly forced to adapt to new conditions. This leads to a revaluation of values. In the process of resolving conflicts and conflicts in social institutions, the system of values is also revised. Such flexibility and dynamic value system is necessary for a person’s personal growth and successful functioning in society. Values act as a beacon that guides a person not only in his inner world, but also in the external world